Systems and management - review - Ross, M (Economic & Social Studies, 1973)
This article seeks to serve several purposes, first to present a brief statement of the evolution and philosophy of modern systems analysis and then, to relate this to the operation of the managerial function in a modern firm. This first objective is necessary to explain the great variety of interpretations to be found in the literature. It is also hoped to demonstrate that the great challenge of the approach and the attendant excitement is no mere passing fad but rather based on the realisation that systems analysis is one of those new ways of looking at familiar things which in all ages have resulted in real advances in the level of scientific understanding.
Keywords: Systems